Designing Improvements in Academic Service Quality in Higher Education Using Transformational Leadership to Foster Work Motivation - Yoniv Erdhianto; Anwar Sodik (CV Firmos, 2026)
The leadership style of university administrators is a key factor contributing to the suboptimal performance of higher education in Indonesia. The effectiveness of lecturers and educational staff is largely influenced by how the rector leads the institution. A rector is expected to drive transformation within the university environment by fostering a strong quality-oriented work culture, while also motivating and supporting the professional development of academic and administrative personnel. This study aims to identify the components of transformational leadership demonstrated by rectors in private engineering universities. A qualitative descriptive approach was employed, involving participants such as rectors, vice rectors, deans, and heads of study programs. Data were collected through interviews, observations, and documentation, and validated using source and method triangulation. The data were analyzed qualitatively using the Miles and Huberman interactive model, which includes data collection, reduction, presentation, and conclusion drawing. The findings reveal that: (1) The rector’s idealized influence is reflected in the involvement of stakeholders in formulating the university’s vision, mission, and programs, as well as in conducting regular meetings to address challenges; (2) Inspirational motivation is demonstrated through the use of flexible leadership styles adapted to different situations; (3) Intellectual stimulation is shown by encouraging efficiency, punctuality, and collaboration in work processes; (4) Individualized consideration is evident in the attention given to the needs of lecturers and educational staff; (5) Overall, the rector’s transformational leadership has proven effective in enhancing work motivation among lecturers and administrative staff.